Acrylic acid pressure-sensitive adhesive for low-surface-energy protective film, preparation method of acrylic acid pressure-sensitive adhesive and protective film

By using an acrylic pressure-sensitive adhesive containing a tackifying resin and crosslinking monomer on a low-surface energy material, and using ultraviolet curing technology, the problem of insufficient adhesion of traditional adhesives on low-surface energy materials is solved, and an efficient and durable bonding effect is achieved.

CN119799173APending Publication Date: 2025-04-11SIDIKE NEW MATERIALS (JIANGSU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411926574.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional acrylic pressure-sensitive adhesives have poor adhesion on low-surface energy materials and are prone to fall off during use, affecting the quality and reliability of the product.

Method used

A pressure-sensitive acrylic adhesive for low-surface energy protective film is used, and its raw material components include tackifying resin, monomer, isooctyl acrylate, initiator and crosslinked monomer, and bonding is achieved through ultraviolet curing technology.

Benefits of technology

Excellent adhesion and durability on low-surface energy materials are achieved, and no glue residue after peeling is left, which significantly improves the quality and service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209390320000111
    Figure BDA0005209390320000111
  • Figure BDA0005209390320000121
    Figure BDA0005209390320000121
Patent Text Reader

Abstract

The invention discloses an acrylic pressure-sensitive adhesive for a low-surface-energy protective film, a preparation method of the acrylic pressure-sensitive adhesive and the protective film. The pressure-sensitive adhesive comprises the following raw material components in parts by weight: 1-5 parts of tackifying resin, 2-20 parts of a first monomer, 35-140 parts of a second monomer, 10-50 parts of 2-ethylhexyl acrylate, 0.02-0.2 part of an initiator and 0.02-0.2 part of a crosslinking monomer. Through combination of the special tackifying resin, the cross-linking monomer and an ultraviolet curing scheme, excellent adhesive strength and durability on a low-surface-energy material are realized, and no adhesive residue is left after stripping after long-time use; the protective film has a simple and convenient construction process and a wide application prospect, and the quality and the service life of a product can be remarkably improved and prolonged. The acrylic pressure-sensitive adhesive for the low-surface-energy protective film does not contain an organic solvent, is green and pollution-free, and has outstanding adhesive property and good creep property on a low-surface-energy material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of protective film materials, and in particular to an acrylic pressure-sensitive adhesive for a low-surface-energy protective film, a preparation method thereof, and the protective film. Background Art

[0002] Low surface energy materials (such as polytetrafluoroethylene, polyethylene, polypropylene, etc.) are widely used in many fields due to their excellent hydrophobicity and oleophobicity, including electronic equipment, automobiles, medical devices, packaging materials, etc. However, the low surface energy of these materials makes it difficult for traditional protective films to form effective adhesion with them, resulting in the protective film easily falling off during use, affecting the quality and service life of the product. These materials have excellent hydrophobicity and oleophobicity and can resist liquid infiltration, but also increase the difficulty of bonding. Among them, HC is commonly used in the screens of some 3C digital products such as mobile phones, tablets, and watches. HC usually refers to hardened protective films, hardened protective films, anti-scratch protective films, etc., which are generally materials with hardened surfaces and have the advantages of high light transmittance, wear resistance, and scratch resistance. With the increasing requirements of the consumer electronics market and the popularity of folding screens, traditional protective films can no longer meet the needs of customers. HC protective films are a major trend in future development. In order to cooperate with the use of HC, the protective film is mainly based on high recovery, its peeling force is uniform and stable, the thickness is uniform, and it has good tensile strength and thermal stability. Because of its heavy peeling force, it can also prevent the protective film from moving or falling off during the processing.

[0003] Since HC is a low surface energy material and the water drop angle is greater than 100, protective films are often used to protect low surface energy materials during use and transportation to prevent scratches and contamination. Traditional protective films and adhesives have poor adhesion on low surface energy materials and are prone to fall off during use, affecting product quality and reliability. Acrylic pressure-sensitive adhesives, as a commonly used adhesive in protective films, have excellent bonding properties to high surface energy materials such as metals and glass, but their bonding properties to low surface energy materials are less than ideal and are prone to debonding and falling off during use, posing certain hidden dangers to the use of downstream products. Therefore, there is a need for an acrylic pressure-sensitive adhesive with excellent bonding properties to low surface energy materials. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an acrylic pressure-sensitive adhesive for a low surface energy protective film, a preparation method thereof and a protective film in view of the deficiencies in the above-mentioned prior art.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: In the first aspect of the present invention, an acrylic pressure-sensitive adhesive for a low surface energy protective film is provided, comprising the following raw material components in parts by weight:

[0006] 1-5 parts of tackifying resin, 2-20 parts of first monomer, 35-140 parts of second monomer, 10-50 parts of isooctyl acrylate, 0.02-0.2 parts of initiator, 0.02-0.2 parts of crosslinking monomer;

[0007] The raw materials for preparing the tackifying resin include, by weight, 15-60 parts of dicyclopentenyl ethyl acrylate, 10-40 parts of methyl methacrylate, 40-170 parts of toluene, 0.1-0.4 parts of AIBN, and 1.5-6 parts of dodecyl mercaptan.

[0008] Preferably, the raw materials for preparing the tackifying resin include, by weight, 30 parts of dicyclopentenyl ethyl acrylate, 20 parts of methyl methacrylate, 85 parts of toluene, 0.2 parts of AIBN, and 3 parts of dodecyl mercaptan.

[0009] Preferably, the tackifying resin is prepared by the following method:

[0010] Dicyclopentenyl ethyl acrylate and methyl methacrylate are added to toluene, nitrogen is introduced at 40-60°C and stirred for 15-60 minutes, then the temperature is raised to 65-72°C, dodecyl mercaptan and part of AIBN are added dropwise, the temperature is maintained and stirred for reaction for 1-4 hours, then the temperature is raised to 75-85°C, the remaining part of AIBN is added, and the reaction is continued for 2-8 hours; after cooling to room temperature, an acrylic acid homopolymer is obtained, the acrylic acid homopolymer is precipitated in methanol and washed, and then vacuum dried at 40-60°C for 12-48 hours to obtain a tackifying resin.

[0011] Preferably, the tackifying resin is prepared by the following method:

[0012] Dicyclopentenyl ethyl acrylate and methyl methacrylate are added to toluene, nitrogen is introduced at 50°C and stirred for 30 minutes, then the temperature is raised to 70°C, dodecyl mercaptan and half the mass of AIBN are added dropwise, the temperature is maintained and stirred for 2 hours, the temperature is raised to 80°C, the remaining half the mass of AIBN is added, and the reaction is continued for 4 hours; after cooling to room temperature, an acrylic acid homopolymer is obtained, the acrylic acid homopolymer is precipitated in methanol and washed, and then vacuum dried at 50°C for 24 hours to obtain a tackifying resin.

[0013] Preferably, the first monomer is selected from at least one of hydroxypropyl acrylate and hydroxyethyl acrylate; and the second monomer is selected from at least one of n-heptyl acrylate and butyl acrylate.

[0014] Preferably, the initiator is selected from at least one of initiator 184 and initiator 651, and the crosslinking monomer is selected from at least one of ethylene glycol diacrylate, 1,6-hexanediol diacrylate, isocyanate, and urethane acrylate.

[0015] Preferably, the raw material components of the acrylic pressure-sensitive adhesive for low surface energy protective film further include 1-4 parts by weight of a third monomer, and the third monomer is selected from at least one of n-heptyl acrylate and butyl acrylate.

[0016] The second aspect of the present invention provides a method for preparing the acrylic pressure-sensitive adhesive for low surface energy protective film as described above, comprising the following steps:

[0017] S1. In a light-proof environment, mix the first monomer, the second monomer, isooctyl acrylate, and part of the initiator, introduce nitrogen, stir for 10-40 minutes, and then irradiate with a UVLED lamp with a light intensity of 2-10mw / cm 2 After the temperature rises by 10-15°C, the light source is turned off and the mixture is cooled to room temperature to obtain acrylic glue;

[0018] S2. In a light-proof condition, add the crosslinking monomer, the remaining initiator, and the tackifying resin into the acrylic glue, mix and stir evenly, and remove bubbles to obtain the acrylic pressure-sensitive adhesive for the low surface energy protective film.

[0019] The third aspect of the present invention provides another method for preparing the acrylic pressure-sensitive adhesive for low surface energy protective film as described above, comprising the following steps:

[0020] S1. In a light-proof environment, mix the first monomer, the second monomer, isooctyl acrylate, and part of the initiator, introduce nitrogen, stir for 10-40 minutes, and then irradiate with a UVLED lamp with a light intensity of 2-10mw / cm 2 After the temperature rises by 10-15°C, the light source is turned off and the mixture is cooled to room temperature to obtain acrylic glue;

[0021] S2. In a light-proof condition, add the cross-linking monomer, the remaining initiator, the tackifying resin, and the third monomer into the acrylic glue, mix and stir evenly, and remove bubbles to obtain the acrylic pressure-sensitive adhesive for the low surface energy protective film.

[0022] A fourth aspect of the present invention provides a low surface energy protective film, which is prepared by the following method:

[0023] The acrylic pressure-sensitive adhesive as described above is evenly coated on the base film, a release film is coated on the adhesive layer to isolate oxygen, and then cured with a UVLED lamp to obtain the low surface energy protective film.

[0024] The beneficial effects of the present invention are:

[0025] The present invention provides an acrylic pressure-sensitive adhesive for a low surface energy protective film and a protective film, wherein the adhesive has excellent appearance, no residual adhesive, is colorless and transparent, has good thermal stability and creep recovery, and has stable peeling properties for low surface energy;

[0026] The present invention achieves excellent adhesion and durability on low surface energy materials by combining special tackifying resin, cross-linking monomer and ultraviolet curing scheme, and no glue residue is left after peeling after long-term use; the protective film has a simple construction process and broad application prospects, and can significantly improve the quality and service life of the product.

[0027] The acrylic pressure-sensitive adhesive for the low surface energy protective film of the present invention does not contain organic solvents, is green and pollution-free, and has outstanding bonding performance and good creep performance for low surface energy materials. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0029] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0030] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0031] The present invention provides an acrylic pressure-sensitive adhesive for a low surface energy protective film, comprising the following raw material components in parts by weight:

[0032] 1-5 parts of tackifying resin, 2-20 parts of first monomer, 35-140 parts of second monomer, 10-50 parts of isooctyl acrylate, 0.02-0.2 parts of initiator, and 0.02-0.2 parts of crosslinking monomer.

[0033] In a preferred embodiment, the raw materials for preparing the tackifying resin include, by weight: 15-60 parts of dicyclopentenyl ethyl acrylate, 10-40 parts of methyl methacrylate, 40-170 parts of toluene, 0.1-0.4 parts of AIBN, and 1.5-6 parts of dodecyl mercaptan. The tackifying resin has excellent adhesion and durability.

[0034] In a preferred embodiment, the raw materials for preparing the tackifying resin include, by weight: 30 parts of dicyclopentenyl ethyl acrylate, 20 parts of methyl methacrylate, 85 parts of toluene, 0.2 parts of AIBN, and 3 parts of dodecyl mercaptan.

[0035] In a preferred embodiment, the tackifying resin is prepared by the following method:

[0036] Dicyclopentenyl ethyl acrylate and methyl methacrylate are added to toluene, nitrogen is introduced at 40-60°C and stirred for 15-60 minutes, then the temperature is raised to 65-72°C, dodecyl mercaptan and part of AIBN are added dropwise, the temperature is maintained and stirred for reaction for 1-4 hours, then the temperature is raised to 75-85°C, the remaining part of AIBN is added, and the reaction is continued for 2-8 hours; after cooling to room temperature, an acrylic acid homopolymer is obtained, the acrylic acid homopolymer is precipitated in methanol and washed, and then vacuum dried at 40-60°C for 12-48 hours to obtain a tackifying resin.

[0037] In a preferred embodiment, the tackifying resin is prepared by the following method:

[0038] Dicyclopentenyl ethyl acrylate and methyl methacrylate are added to toluene, nitrogen is introduced at 50°C and stirred for 30 minutes, then the temperature is raised to 70°C, dodecyl mercaptan and half the mass of AIBN are added dropwise, the temperature is maintained and stirred for 2 hours, the temperature is raised to 80°C, the remaining half the mass of AIBN is added, and the reaction is continued for 4 hours; after cooling to room temperature, an acrylic acid homopolymer is obtained, the acrylic acid homopolymer is precipitated in methanol and washed, and then vacuum dried at 50°C for 24 hours to obtain a tackifying resin.

[0039] In a preferred embodiment, the first monomer is selected from at least one of hydroxypropyl acrylate and hydroxyethyl acrylate.

[0040] In a preferred embodiment, the second monomer is selected from at least one of n-heptyl acrylate and butyl acrylate.

[0041] In a preferred embodiment, the initiator is selected from at least one of Initiator 184 (1-hydroxycyclohexylphenyl ketone) and Initiator 651 (2,2-dimethoxy-2-phenylacetophenone).

[0042] In a preferred embodiment, the bifunctional cross-linking monomer is selected from at least one of 1,6-hexanediol diacrylate and ethylene glycol diacrylate. Adding the cross-linking monomer can increase the cross-linking density of the resin and enhance the mechanical properties and chemical resistance of the protective film.

[0043] The present invention also provides a method for preparing the acrylic pressure-sensitive adhesive for the low surface energy protective film, comprising the following steps:

[0044] S1. In a light-proof environment, mix the first monomer, the second monomer, isooctyl acrylate, and part of the initiator, introduce nitrogen, stir for 10-40 minutes, and then irradiate with a UVLED lamp with a light intensity of 2-10mw / cm 2 After the temperature rises by 10-15°C, the light source is turned off and the mixture is cooled to room temperature to obtain acrylic glue;

[0045] S2. Under light-proof conditions, add the crosslinking monomer, the remaining initiator, and the tackifying resin to the acrylic glue, mix and stir evenly, and remove bubbles to obtain an acrylic pressure-sensitive adhesive for a low surface energy protective film. In the present invention, ultraviolet light curing technology is used to achieve rapid curing and improve production efficiency.

[0046] In a preferred embodiment, the raw material components of the acrylic pressure-sensitive adhesive for low surface energy protective film further include 1-4 parts by weight of a third monomer, and the third monomer is selected from at least one of n-heptyl acrylate and butyl acrylate. At this time, the preparation method of the acrylic pressure-sensitive adhesive for low surface energy protective film includes the following steps:

[0047] S1. In a light-proof environment, mix the first monomer, the second monomer, isooctyl acrylate, and part of the initiator, introduce nitrogen, stir for 10-40 minutes, and then irradiate with a UVLED lamp with a light intensity of 2-10mw / cm 2 After the temperature rises by 10-15°C, the light source is turned off and the mixture is cooled to room temperature to obtain acrylic glue;

[0048] S2. In a light-proof condition, add the cross-linking monomer, the remaining initiator, the tackifying resin, and the third monomer into the acrylic glue, mix and stir evenly, and remove bubbles to obtain an acrylic pressure-sensitive adhesive for a low surface energy protective film.

[0049] The present invention also provides a low surface energy protective film, which is prepared by the following method:

[0050] The acrylic pressure-sensitive adhesive is evenly coated on the base film, a release film is covered on the adhesive layer to isolate oxygen, and then cured with a UVLED lamp to obtain a low surface energy protective film.

[0051] The present invention regulates and stably synthesizes acrylic resin through UV polymerization, thereby achieving control over the performance of acrylic ester glue; the tackifying resin prepared by the present invention has a higher degree of compatibility with polar monomers in UV polymerization and has relatively excellent performance; the present invention can solve the performance defect problem of the adhesive film by adjusting the formula and process during secondary curing.

[0052] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0053] Example 1

[0054] A low surface energy protective film, the preparation method of which comprises the following steps:

[0055] S1. Accurately weigh 5 parts of hydroxypropyl acrylate, 25 parts of isooctyl acrylate, 70 parts of n-heptyl acrylate, and 0.06 parts of 184 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen gas through the flask and stir for 20 minutes. Then irradiate with a UVLED lamp at a light intensity of 5 mw / cm 2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0056] S2. Under light-proof conditions, accurately weigh 0.04 parts of 184, 0.04 parts of 1,6-hexanediol diacrylate, and 3 parts of tackifying resin, add them into acrylic glue, mix and stir evenly; remove bubbles with a vacuum machine to obtain an acrylic pressure-sensitive adhesive for a low surface energy protective film.

[0057] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 9600mj / cm 2 The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0058] Example 2

[0059] A low surface energy protective film, the preparation method of which comprises the following steps:

[0060] S1. In a light-proof environment, accurately weigh 5 parts of hydroxyethyl acrylate, 25 parts of isooctyl acrylate, 70 parts of butyl acrylate, and 0.06 parts of 184 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen gas and stir for 20 minutes before irradiating with a UVLED lamp at a light intensity of 5 mw / cm 2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0061] Under light-proof conditions, accurately weigh 0.04 parts of 184, 0.04 parts of 1,6-hexanediol diacrylate, 0.04 parts of acrylic acid urethane, and 3 parts of tackifying resin, add them into acrylic glue, mix and stir evenly; after removing bubbles with a vacuum machine, obtain an acrylic pressure-sensitive adhesive for low surface energy protective film.

[0062] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 9600mj / cm 2 The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0063] Example 3

[0064] A low surface energy protective film, the preparation method of which comprises the following steps:

[0065] S1. In a light-proof environment, accurately weigh 5 parts of hydroxypropyl acrylate, 30 parts of isooctyl acrylate, 65 parts of n-heptyl acrylate, and 0.06 parts of 651 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen gas and stir for 20 minutes before irradiating with a UVLED lamp at a light intensity of 5 mw / cm 2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0066] S2. Under light-proof conditions, accurately weigh 0.04 parts of 184, 0.04 parts of ethylene glycol diacrylate, and 2 parts of tackifying resin, add them into acrylic glue, mix and stir evenly; remove bubbles with a vacuum machine to obtain an acrylic pressure-sensitive adhesive for a low surface energy protective film.

[0067] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 9600mj / cm 2 The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0068] Example 4

[0069] A low surface energy protective film, the preparation method of which comprises the following steps:

[0070] S1. In a light-proof environment, accurately weigh 5 parts of hydroxypropyl acrylate, 5 parts of hydroxyethyl acrylate, 45 parts of n-heptyl acrylate, 45 parts of isooctyl acrylate, and 0.06 parts of 651 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen gas and stir for 20 minutes before irradiating with a UVLED lamp with a light intensity of 5 mw / cm 2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0071] S2. Under light-proof conditions, accurately weigh 0.04 parts of 651, 0.08 parts of ethylene glycol diacrylate, 5 parts of tackifying resin, and 2 parts of hydroxyethyl acrylate, add them into acrylic glue, mix and stir evenly; remove bubbles with a vacuum machine to obtain an acrylic pressure-sensitive adhesive for a low surface energy protective film.

[0072] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 9600mj / cm 2The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0073] Example 5

[0074] A low surface energy protective film, the preparation method of which comprises the following steps:

[0075] S1. In a light-proof environment, accurately weigh 8 parts of hydroxypropyl acrylate, 25 parts of isooctyl acrylate, 67 parts of n-heptyl acrylate, and 0.06 parts of 184 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen gas and stir for 20 minutes before irradiating with a UVLED lamp at a light intensity of 5 mw / cm 2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0076] S2. Under light-proof conditions, accurately weigh 0.04 parts of 184, 0.06 parts of ethylene glycol diacrylate, 3 parts of tackifying resin, and 2 parts of N-vinyl pyrrolidone, add them into acrylic glue, mix and stir evenly; remove bubbles with a vacuum machine to obtain an acrylic pressure-sensitive adhesive for low surface energy protective film.

[0077] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 9600mj / cm 2 The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0078] Comparative Example 1

[0079] A low surface energy protective film, the preparation method of which comprises the following steps:

[0080] S1. In a light-proof environment, accurately weigh 5 parts of hydroxypropyl acrylate, 25 parts of isooctyl acrylate, 10 parts of butyl acrylate, 60 parts of n-heptyl acrylate, and 0.06 parts of 184 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen gas and stir for 20 minutes before irradiating with a UVLED lamp at a light intensity of 5 mw / cm 2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0081] S2. Under light-proof conditions, accurately weigh 0.04 parts of 184, 0.04 parts of 1,6-hexanediol diacrylate, 0.04 parts of isocyanate, and 3 parts of tackifying resin, add them into acrylic glue, mix and stir evenly; remove bubbles with a vacuum machine to obtain an acrylic pressure-sensitive adhesive for a low surface energy protective film.

[0082] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 9600mj / cm 2 The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0083] Comparative Example 2

[0084] A low surface energy protective film, the preparation method of which comprises the following steps:

[0085] S1. In a light-proof environment, accurately weigh 5 parts of hydroxypropyl acrylate, 25 parts of isooctyl acrylate, 70 parts of n-heptyl acrylate, and 0.06 parts of 651 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen and stir for 20 minutes before irradiating with a UVLED lamp. The light intensity is set to 5 mw / cm 2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0086] S2. Under light-proof conditions, accurately weigh 0.04 parts of 651, 0.08 parts of isocyanate, 0.04 parts of 1,6-hexanediol diacrylate, and 3 parts of tackifying resin, add them into acrylic glue, mix and stir evenly; remove bubbles with a vacuum machine to obtain an acrylic pressure-sensitive adhesive for a low surface energy protective film.

[0087] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 9600mj / cm 2 The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0088] Comparative Example 3

[0089] A low surface energy protective film, the preparation method of which comprises the following steps:

[0090] S1. In a light-proof environment, accurately weigh 5 parts of hydroxypropyl acrylate, 5 parts of hydroxyethyl propionate, 5 parts of butyl acrylate, 40 parts of n-heptyl acrylate, 45 parts of isooctyl acrylate, and 0.06 parts of 184 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen gas, stir for 20 minutes, and then irradiate with a UVLED lamp with a light intensity of 5 mw / cm 2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0091] S2. Under light-proof conditions, accurately weigh 0.04 parts of 184, 0.04 parts of ethylene glycol diacrylate, and 5 parts of tackifying resin, add them into acrylic glue, mix and stir evenly; remove bubbles with a vacuum machine to obtain an acrylic pressure-sensitive adhesive for a low surface energy protective film.

[0092] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 9600mj / cm 2 The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0093] Comparative Example 4

[0094] A low surface energy protective film, the preparation method of which comprises the following steps:

[0095] S1. In a light-proof environment, accurately weigh 10 parts of hydroxyethyl acrylate, 60 parts of isooctyl acrylate, 10 parts of n-heptyl acrylate, and 0.06 parts of 184 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen gas and stir for 20 minutes before irradiating with a UVLED lamp at a light intensity of 5 mw / cm 2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0096] S2. Under light-proof conditions, accurately weigh 0.04 parts of 184, 0.06 parts of ethylene glycol diacrylate, 0.04 parts of acrylic urethane, 5 parts of tackifying resin, and 2 parts of N-vinyl pyrrolidone, add them into acrylic glue, mix and stir evenly; remove bubbles with a vacuum machine to obtain an acrylic pressure-sensitive adhesive for low surface energy protective film.

[0097] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 9600mj / cm 2 The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0098] Comparative Example 5

[0099] A low surface energy protective film, the preparation method of which comprises the following steps:

[0100] S1. In a light-proof environment, accurately weigh 5 parts of hydroxyethyl acrylate, 25 parts of isooctyl acrylate, 70 parts of butyl acrylate, and 0.06 parts of 184 and place them in a four-necked flask equipped with a stirrer, a thermometer, and a nitrogen tube. Pass nitrogen gas and stir for 20 minutes before irradiating with a UVLED lamp at a light intensity of 5 mw / cm2 The reaction begins when the temperature starts to rise rapidly. After the temperature rises by 15°C and the glue reaches a suitable consistency, turn off the light source and wait for it to automatically cool to room temperature to obtain acrylic glue.

[0101] S2. Under light-proof conditions, accurately weigh 0.04 parts of 184, 0.06 parts of 1,6-hexanediol diacrylate, and 3 parts of tackifying resin, add them into acrylic glue, mix and stir evenly; remove bubbles with a vacuum machine to obtain an acrylic pressure-sensitive adhesive for a low surface energy protective film.

[0102] S3, apply the low surface energy protective film with acrylic pressure-sensitive adhesive on a 50μm thick release film, and then cover the surface with another layer of release film to isolate oxygen; use energy of 5600mj / cm 2 The UVLED lamp is used for secondary curing. After curing, a low surface energy protective film with a dry glue thickness of 35μm is obtained, and the performance is measured.

[0103] The relevant performance test methods are as follows:

[0104] 30min, 24H HC peeling force test method: the prepared acrylic pressure-sensitive adhesive was transferred to the AR silicone film, the AR silicone surface was pre-plated with Plassma, and the sample was prepared according to GB / T 2792-2014 standard; the sample was attached to the HC film, rolled back and forth twice with a 2kg roller (600mm / min), degassed in a 0.3Mpa, 55℃ vacuum degassing machine for 15min, and then placed at room temperature (23±2℃, relative humidity 50%) for 30min and 24H, and then peeled 180° at 300mm / min using a universal tensile testing machine.

[0105] Haze test method: According to JISK-7105 standard, use Nippon Denshoku NDH2000N haze meter and use the transmitted light method to measure.

[0106] Creep test: Use a creep tester that meets the standard requirements to ensure the accuracy and stability of the equipment. Set a constant stress level according to the standard or actual application requirements. Common stress levels range from 0.1MPa to 1.0MPa. Set the test temperature according to the actual use conditions, usually room temperature (23℃) or high temperature (such as 80℃). Record deformation data, draw creep curves, and calculate creep rate and creep rupture time.

[0107] The test results are shown in Table 1 below:

[0108] Table 1

[0109]

[0110]

[0111] According to the test data of Comparative Example 1 and Example 1, the peeling force of the protective film is significantly improved in Comparative Example 1, but there is residual glue in the 24H peeling force. The reason is that when the other components remain unchanged, adding isocyanate and butyl acrylate to the components will have a greater impact on the peeling force and creep.

[0112] According to the test data of Example 1, Example 2 and Comparative Example 3, the amount of tackifying resin has a significant effect on the peel force and haze, and the polar monomers (hydroxyethyl acrylate and hydroxypropyl acrylate) have a good solubility in the tackifying resin, so adding polar monomers can effectively reduce the haze of the film.

[0113] According to Example 2, Comparative Example 4 and Comparative Example 5, it can be seen that the bifunctional short-chain cross-linking monomer (1,6-hexanediol diacrylate, ethylene glycol diacrylate, wherein the ethylene glycol diacrylate chain is shorter and the degree of cross-linking in the system is relatively good) has a greater influence on the creep recovery rate. The main reason is that the cohesion of the pressure-sensitive adhesive increases, while the reduction of UV curing energy will lead to incomplete curing and reduced cohesion.

[0114] According to the test data of Examples 2 and 3, the creep recovery of Example 3 is significantly reduced, which is mainly due to the influence of the proportions of soft monomers (butyl acrylate, isooctyl acrylate, n-heptyl acrylate) and functional monomers (hydroxyethyl acrylate, hydroxypropyl acrylate, 1,6-hexanediol diacrylate, ethylene glycol diacrylate, N-vinyl pyrrolidone), and the peel force is significantly improved, indicating that the network structure formed by the polymerization of the difunctional short-chain cross-linking monomer (ethylene glycol diacrylate) has better adhesion and wettability to the protective film.

[0115] According to the test data of Example 2 and Comparative Example 2, the peeling force of Comparative Example 2 is significantly improved and the creep recovery rate is reduced. The reason is that the amount of cross-linking monomer added in Comparative Example 2 is increased, the cross-linking degree is enhanced, and the small molecule structure is increased.

[0116] The reaction results of Example 3 and Example 5 show that the reaction efficiency of photoinitiator 651 is higher than that of 184, but it has little effect on the performance.

[0117] According to the test data of Example 4, Example 5 and Comparative Example 4, the tackifying resin will improve the adhesion to the protective film, but there will be residual glue and affect the optical properties. The polar monomers (hydroxyethyl acrylate, hydroxypropyl acrylate, N-vinyl pyrrolidone) have good solubility in the tackifying resin. The stronger the polarity, the lower the haze of the film after curing.

[0118] The various tests of Examples 1-5 show that their performance is relatively excellent and there is no residual glue phenomenon.

[0119] Comparative Example 1 and Comparative Example 2 have problems such as reduced peeling force and reduced creep recovery due to the difference in monomer ratio and the addition of polar monomers.

[0120] Comparative Example 3 changes the monomer ratio, the peeling force is improved but there is a problem of residual glue and the haze is relatively high.

[0121] In Comparative Example 4, after the polar monomer is replaced (hydroxyethyl acrylate is replaced with N-vinyl pyrrolidone), the haze is relatively excellent, but there is still residual glue.

[0122] In Comparative Example 5, the peeling force decreased after the UV curing energy was reduced, and the curing was incomplete with small molecules remaining.

[0123] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. An acrylic pressure-sensitive adhesive for a low surface energy protective film, characterized in that: The invention comprises the following raw material components by weight: 1-5 parts of tackifying resin, 2-20 parts of first monomer, 35-140 parts of second monomer, 10-50 parts of isooctyl acrylate, 0.02-0.2 parts of initiator, 0.02-0.2 parts of crosslinking monomer; The raw materials for preparing the tackifying resin include, by weight, 15-60 parts of dicyclopentenyl ethyl acrylate, 10-40 parts of methyl methacrylate, 40-170 parts of toluene, 0.1-0.4 parts of AIBN, and 1.5-6 parts of dodecyl mercaptan.

2. The acrylic pressure-sensitive adhesive for low surface energy protective film according to claim 1, characterized in that: The raw materials for preparing the tackifying resin include, by weight, 30 parts of dicyclopentenyl ethyl acrylate, 20 parts of methyl methacrylate, 85 parts of toluene, 0.2 parts of AIBN, and 3 parts of dodecyl mercaptan.

3. The acrylic pressure-sensitive adhesive for low surface energy protective film according to claim 1, characterized in that: The tackifying resin is prepared by the following method: Dicyclopentenyl ethyl acrylate and methyl methacrylate are added to toluene, nitrogen is introduced at 40-60°C and stirred for 15-60 minutes, then the temperature is raised to 65-72°C, dodecyl mercaptan and part of AIBN are added dropwise, the temperature is maintained and stirred for reaction for 1-4 hours, then the temperature is raised to 75-85°C, the remaining part of AIBN is added, and the reaction is continued for 2-8 hours; after cooling to room temperature, an acrylic acid homopolymer is obtained, the acrylic acid homopolymer is precipitated in methanol and washed, and then vacuum dried at 40-60°C for 12-48 hours to obtain a tackifying resin.

4. The acrylic pressure-sensitive adhesive for low surface energy protective film according to claim 3, characterized in that: The tackifying resin is prepared by the following method: Dicyclopentenyl ethyl acrylate and methyl methacrylate are added to toluene, nitrogen is introduced at 50°C and stirred for 30 minutes, then the temperature is raised to 70°C, dodecyl mercaptan and half the mass of AIBN are added dropwise, the temperature is maintained and stirred for 2 hours, the temperature is raised to 80°C, the remaining half the mass of AIBN is added, and the reaction is continued for 4 hours; after cooling to room temperature, an acrylic acid homopolymer is obtained, the acrylic acid homopolymer is precipitated in methanol and washed, and then vacuum dried at 50°C for 24 hours to obtain a tackifying resin.

5. The acrylic pressure-sensitive adhesive for low surface energy protective film according to claim 1, characterized in that: The first monomer is selected from at least one of hydroxypropyl acrylate and hydroxyethyl acrylate; the second monomer is selected from at least one of n-heptyl acrylate and butyl acrylate.

6. The acrylic pressure-sensitive adhesive for low surface energy protective film according to claim 1, characterized in that: The initiator is selected from at least one of initiator 184 and initiator 651, and the crosslinking monomer is selected from at least one of ethylene glycol diacrylate, 1,6-hexanediol diacrylate, isocyanate, and acrylic urethane.

7. The acrylic pressure-sensitive adhesive for low surface energy protective film according to claim 1, characterized in that: The raw material components also include 1-4 parts by weight of a third monomer, and the third monomer is selected from at least one of n-heptyl acrylate and butyl acrylate.

8. A method for preparing the acrylic pressure-sensitive adhesive for low surface energy protective film according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. In a light-proof environment, mix the first monomer, the second monomer, isooctyl acrylate, and part of the initiator, introduce nitrogen, stir for 10-40 minutes, and then irradiate with a UVLED lamp with a light intensity of 2-10mw / cm 2 After the temperature rises by 10-15°C, the light source is turned off and the mixture is cooled to room temperature to obtain acrylic glue; S2. In a light-proof condition, add the crosslinking monomer, the remaining initiator, and the tackifying resin into the acrylic glue, mix and stir evenly, and remove bubbles to obtain the acrylic pressure-sensitive adhesive for the low surface energy protective film.

9. A method for preparing the acrylic pressure-sensitive adhesive for low surface energy protective film according to claim 7, characterized in that: The following steps are involved: S1. In a light-proof environment, mix the first monomer, the second monomer, isooctyl acrylate, and part of the initiator, introduce nitrogen, stir for 10-40 minutes, and then irradiate with a UVLED lamp with a light intensity of 2-10mw / cm 2 After the temperature rises by 10-15°C, the light source is turned off and the mixture is cooled to room temperature to obtain acrylic glue; S2. In a light-proof condition, add the cross-linking monomer, the remaining initiator, the tackifying resin, and the third monomer into the acrylic glue, mix and stir evenly, and remove bubbles to obtain the acrylic pressure-sensitive adhesive for the low surface energy protective film.

10. A low surface energy protective film, characterized in that: It is prepared by the following method: The acrylic pressure-sensitive adhesive as claimed in any one of claims 1 to 9 is uniformly coated on a base film, a release film is coated on the adhesive layer to isolate oxygen, and then cured with a UVLED lamp to obtain the low surface energy protective film.